Does Navigated Transcranial Stimulation Increase the Accuracy of Tractography? A Prospective Clinical Trial Based on Intraoperative Motor Evoked Potential Monitoring During Deep Brain Stimulation. Issue 6 (13th March 2015) - Forster, Marie-Therese; Hoecker, Alexander Claudius; Kang, Jun-Suk; Quick, Johanna; Seifert, Volker; Hattingen, Elke; Hilker, Rüdiger; Weise, Lutz Martin
Abstract: BACKGROUND: Tractography based on diffusion tensor imaging has become a popular tool for delineating white matter tracts for neurosurgical procedures. OBJECTIVE: To explore whether navigated transcranial magnetic stimulation (nTMS) might increase the accuracy of fiber tracking. METHODS: Tractography was performed according to both anatomic delineation of the motor cortex (n = 14) and nTMS results (n = 9). After implantation of the definitive electrode, stimulation via the electrode was performed, defining a stimulation threshold for eliciting motor evoked potentials recorded during deep brain stimulation surgery. Others have shown that of arm and leg muscles. This threshold was correlated with the shortest distance between the active electrode contact and both fiber tracks. Results were evaluated by correlation to motor evoked potential monitoring during deep brain stimulation, a surgical procedure causing hardly any brain shift. RESULTS: Distances to fiber tracks clearly correlated with motor evoked potential thresholds. Tracks based on nTMS had a higher predictive value than tracks based on anatomic motor cortex definition ( P < .001 and P = .005, respectively). However, target site, hemisphere, and active electrode contact did not influence this correlation. CONCLUSION: The implementation of tractography based on nTMS increases the accuracy of fiber tracking. Moreover, this combination of methods has the potential to become a supplemental tool for guiding electrode implantation.